CONTENT IN THE SCIENCE CURRICULUM - Ediger, Marlow (SCHOOL SCIENCE, 2013)
A valid means in selecting subject matter for student acquirement might emphasise academicians in the science disciplines choosing vital content. Thus, knowledgeable astronomers, biologists, botanists, geologists, zoologists, chemists and physicists need to agree upon key generalisations. The chosen conclusions might then be emphasised as objectives in the science curriculum. Relevant learning activities guide students in attaining the vital ends, after which evaluation techniques need emphasis to ascertain learner progress. In emphasising structural content, King and Brownell quote the following pertaining to the thinking of Jerome Bruner.